2013
DOI: 10.7149/opa.46.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ACPA on the stability of holographic transmission gratings stored in photopolymers

Abstract: RESUMEN:Este trabajo presenta los resultados obtenidos después de almacenar redes holográficas por transmisión con una frecuencia espacial de 954 líneas/mm y 2663 líneas/mm, en un material basado en PVA/AA. A la composición del material se le ha incorporado un agente acortador de cadenas, el 4,4´-azobis(4-cyanopentanoic acid) (ACPA) para mejorar la respuesta del material a la resolución espacial. Además, se ha aplicado un proceso de curado a las redes almacenadas para fijar el rendimiento en difracción y que n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This composition provides diffraction efficiencies of 100% for holographic gratings with a spatial frequency of 1000 lines/mm. However, previous studies have shown that when you want to store holographic gratings with higher spatial frequencies, the diffraction efficiency decreases as the spatial frequency increases, and falls to a very small diffraction efficiency for spatial frequencies of 5000 lines/mm [22,28].…”
Section: Preparation Of the Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…This composition provides diffraction efficiencies of 100% for holographic gratings with a spatial frequency of 1000 lines/mm. However, previous studies have shown that when you want to store holographic gratings with higher spatial frequencies, the diffraction efficiency decreases as the spatial frequency increases, and falls to a very small diffraction efficiency for spatial frequencies of 5000 lines/mm [22,28].…”
Section: Preparation Of the Materialsmentioning
confidence: 98%
“…However, previous studies have shown that when you want to store holographic gratings with higher spatial frequencies, the diffraction efficiency decreases as the spatial frequency increases, and falls to a very small diffraction efficiency for spatial frequencies of 5000 lines/mm [22,29]. Fortunately, photopolymers are very versatile and it is possible to add new components to their composition.…”
Section: Preparation Of the Materialsmentioning
confidence: 99%